Pengaruh Corporate Governance, Kinerja Lingkungan, dan Ukuran Perusahaan Terhadap Pengungkapan CSR - Adinda Purnama Syane; Jaeni Jaeni (Ekonomis: Journal of Economics and Business, 2021)
This study aims to analyze the effect of institutional ownership, managerial ownership, environmental performance, and firm size on CSRD. CSRD measurement based on GRI-G4 is seen from the company's annual report. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange 2017-2019, which are 492 companies. The research sample was taken using a purposive sampling technique, with observations for 3 years. So, the number of samples studied were 73 companies. Hypothesis testing in this study using multiple regression analysis. The results showed that corporate governance, namely institutional ownership and managerial ownership, had no effect on CSRD. While the environment has a positive effect on CSRD and company size has no effect on CSRD companies.